ANALISIS QUALITY OF SERVICE DENGAN METODE WALK TEST TERHADAP PENGARUH POSISI PENGAMBILAN DATA USER PADA EVENT MOBILE LEGEND TELKOMSEL - Alit Asmaul Fauzi . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2019)
Satisfaction in playing games is highly sought after for game lovers in the world, especially online games, online games require users to have a fast internet connection so that online games remain stable when played, research is done to be able to know the quality of internet network speed needed so that the stability of the internet network can be maintained such as searching for the value of QoS ( quality of service ) and its parameters, namely delay, throughput, jitter, packet loss and delay and the research conducted is focused on the mobile legend event held by Telkomsel using the walk test method . Based on the measurements carried out there are a lot of measurement data that show the quality of delay values which often show numbers on a bad scale and on the first day 4g (1st floor before event delay 473 ms, and during the event   first day 4g (1st floor at the event) 96 ms, second day 4g (1st floor before the event) 318 ms, during the event second day 4g (1st floor at event 86.6 ms, second day 3g (2nd floor before event) 597 ms, and at second day 3g (2nd floor at the event) 96 ms, second day 4g (2nd floor before the event) ms, at the time second day 4g (2nd floor at event) 78.6 ms, second day 4g (3rd floor before event 449 ms, then second day 4g (3rd floor at the event) 94 ms At jitter before the event takes place in a good category that ranges from 21 ms - 74.3 ms and when the event takes place in the category is very good ranging from 0.2 ms - 1.6 ms At the time before the value event packet loss is in a very good category ranging from 0% - 0.6% and when the event takes place in a very good category ranging from 0% - 0.5% At the time before the event throughput also entered a very good category ranging from 94 bps - 1010 bps. then at the time of the event the category was very good ranging between 117 bps - 610 bps